2020
DOI: 10.1016/j.ajpath.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-149* Suppresses Liver Cancer Progression by Down-Regulating Tumor Necrosis Factor Receptor 1–Associated Death Domain Protein Expression

Abstract: Liver cancer is the third leading cause of cancer-related death worldwide. Herein, we show that miR-149* serves as a novel tumor suppressor for liver tumorigenesis. Mice with genetic deletion of miR-149* (miR-149* À/À mice), which caused loss of both miR-149 and miR-149*, were considerably more susceptible to acute liver injury and hepatic carcinogenesis induced by diethylnitrosamine than wild-type mice, accompanied by increased compensatory proliferation and up-regulated gene expression of certain inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…We recently showed that miR-206 is transferred by satellite cell EVs to fibrogenic cells during MOV to regulate collagen deposition, 7 and confirm here that miR-206 is the most abundant miRNA in MPC EVs ( Figure 2C ). Expanding on our earlier work, we found numerous miRNAs enriched in MPC EVs ( Figure 2C ) that are experimentally shown to lower Mmp9 expression, such as miR-24, 47–49 miR-149, 50–55 and miR-486, 56 , 57 as well as miRNAs that are validated to target the 3′-UTR of Mmp9 mRNA and reduce transcript levels, including Let-7e, 58 miR-133a and -133b, 59 , 60 and miR-320 61 ( Figure 2D ). In silico predicted miRNA-mRNA target analysis 62 further revealed that ECM remodeling is the most regulated process by MPC EV miRNAs ( Figure 2E , Tables S2 and S3 ).…”
Section: Resultssupporting
confidence: 68%
“…We recently showed that miR-206 is transferred by satellite cell EVs to fibrogenic cells during MOV to regulate collagen deposition, 7 and confirm here that miR-206 is the most abundant miRNA in MPC EVs ( Figure 2C ). Expanding on our earlier work, we found numerous miRNAs enriched in MPC EVs ( Figure 2C ) that are experimentally shown to lower Mmp9 expression, such as miR-24, 47–49 miR-149, 50–55 and miR-486, 56 , 57 as well as miRNAs that are validated to target the 3′-UTR of Mmp9 mRNA and reduce transcript levels, including Let-7e, 58 miR-133a and -133b, 59 , 60 and miR-320 61 ( Figure 2D ). In silico predicted miRNA-mRNA target analysis 62 further revealed that ECM remodeling is the most regulated process by MPC EV miRNAs ( Figure 2E , Tables S2 and S3 ).…”
Section: Resultssupporting
confidence: 68%
“…Hsa-mir-149 blocked paracrine interactions of macrophages via decreasing the expression of colony-stimulating factor-1 and epidermal growth factor, which could suppress breast cancer metastasis [31]. In liver cancer, mir-149 suppressed tumor progression by restraining the expression of tumor necrosis factor receptor type 1associated death domain protein in NF-κB signaling pathway [32]. Interestingly, in present study, higher expression of hsa-miR-149 meant worse prognosis in HCC.…”
Section: Discussionmentioning
confidence: 47%
“…miR-149 has been confirmed to play an important role in the occurrence and development of a variety of malignant tumors, and has the function of tumor suppressor gene. Feng et al using the miRNA gene chip technology to filtered may participate in regulating the liver metastasis of microRNAs, the results showed that the expression of miR-149 abnormal amount is reduced, at the same time the research by qRT-PCR method in patients with liver cancer and normal plasma, found that miR-149 expression in liver cancer patients plasma and tissue levels significantly lower than normal plasma and corresponding normal tissue adjacent to carcinoma [ 21 ]. Schaefer et al showed that the expression of miR-149 in prostate cancer tissues was significantly lower than that in corresponding adjacent normal tissues through miRNA microarray technology, and the results were verified by QRT PCR method to further confirm its authenticity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%